THE USE OF DIGITAL TECHNOLOGIES INTEACHING RUSSIAN AS A FOREIGNLANGUAGE - Yuldasheva Madina Anvarovna (Western European Studies, 2025)
This article explores the growing role of digital technologies in the teaching of Russian as a foreign language (RFL). With the advancement of educational technology, there has been a noticeable shift in pedagogical approaches that prioritize interactivity, accessibility, and learner-centered methodologies. By integrating audiovisual content, gamification elements, adaptive learning algorithms, and cloud-based communication tools, educators can enhance student motivation, promote autonomous learning, and address the diverse needs of multilingual classrooms. The article presents case studies and empirical evidence demonstrating the successful application of digital resources in both synchronous and asynchronous learning environments. These examples illustrate improvements in students' linguistic competence, engagement, and cultural awareness when digital platforms are strategically incorporated into the curriculum. Furthermore, the study underscores the importance of professional development for teachers to effectively implement and adapt to emerging technologies.
Keywords: Russian as a Foreign Language; digital education technologies; interactive pedagogy